The Impact of Brand Personality towards Customer Loyalty at Pt. Agro Makmur Raya Medan : Pengaruh Kepribadian Merek Terhadap Loyalitas Pelanggan Pada Pt. Agro Makmur Raya Medan - Tina Linda; Devia Febrina; Jung Sen; Kuandi Chandra; Jimmy Kelana (Jurnal Kolaboratif Sains, 2024)
The aim of this research is to analyse the impact of brand personality towards customer loyalty at PT. Agro Makmur Raya, Medan. The research method that the writer use is descriptive method and correlative research. To answer the problem, data is collected by questionnaire to 50 respondents that consist of the customers of PT. Agro Makmur Raya. The SPSS Version 22 is to use to test the data. The writer uses some methods to analyse the data gained, such as: validity, reliability, descriptive method, normality test, correlation test, regression equation, determination of coefficient analysis and z test. Based on the SPSS Version 22 analysis, some conclusions can be made, i.e: 10 questionnaires that the writer use have a good data of reliability and the data are normally distributed. While the correlation test found that the brand personality has strong and positive impact towards customer loyalty at PT. Agro Makmur Raya, Medan. For the determination of variable x and variable y is 76.6% shows that the value of customer loyalty is impact by the value of brand personality. From the test of hypothesis, we can found that for the Alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Based on the result of the analysis, it is concluded that there is impact between brand personality and customer loyalty at PT. Agro Makmur Raya, Medan.